Dehydroxylation Kinetics of Clay Minerals and Its Application to Friction Heating Along an Imbricate Thrust in an Accretionary Prism. (6th September 2018) - Masumoto, Hirokazu; Kameda, Jun; Arima, Hiroshi; Sugiyama, Kazumasa; Nagai, Takaya; Yamamoto, Yuzuru
Abstract: Dehydroxylation of clay minerals within fault gouges is significant for assessing transient thermogenesis due to high‐velocity, frictional slip along fault zones. The clay minerals kaolinite and chlorite are common in fault zones hosted in sedimentary rocks at subduction margins. To better understand the dehydroxylation processes of these clay minerals, high‐temperature X‐ray diffraction analyses were carried out by using a 1:1 mixture of kaolinite and chlorite standard samples. We evaluated the kinetic parameters of each dehydroxylation reaction by thermogravimetric analysis using the Friedman method. For kaolinite, the thermogravimetric data are fitted with a one and a half order equation ( F 3/2 ) with an activation energy of 171 kJ/mol and a frequency factor of 5.6 × 10 8  s −1 . The data for chlorite are analyzed by the geometrical contracting model equation ( R 2 ) with an activation energy of 197 kJ/mol and a frequency factor of 4.5 × 10 9  s −1 . Thermal models of frictional heating employing this calibration show that the frictional heating can explain the reported clay mineralogy in a fossil imbricate thrust from a shallow part in an ancient accretionary prism (Shirako Fault, Japan). This result supports the previous assertion, and the observed temperature anomaly appears to demonstrate the frictional heating caused by coseismic slip on this fault. Key Points: Dehydroxylations of kaolinite and chlorite were investigated by high‐temperature XRD and thermogravimetric experiments Thermal models of frictional heating can reasonably explain the clay mineralogical anomaly of a fault zone deduced from XRD Dehydroxylation of kaolinite and chlorite can be a new proxy to constrain parameters of earthquake slip